2006
DOI: 10.1177/0003319706293146
|View full text |Cite
|
Sign up to set email alerts
|

An Electrocardiographic Algorithm for Determining the Location of Pacemaker Electrode in Patients With Right Bundle Branch Block Configuration During Permanent Ventricular Pacing

Abstract: The expected morphology of right ventricular pacing is a left bundle branch block (LBBB) pattern. However, right bundle branch block (RBBB) can also be seen during permanent right ventricular pacing. The aim of this study was to develop an electrocardiographic algorithm to differentiate this benign condition from septal and free wall perforation with subsequent left ventricular pacing. Three hundred consecutive patients who had permanent ventricular or dual-chamber pacemaker implantation between 1999 and 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
2
33
1
Order By: Relevance
“…Okmen et al [7] (300 patients) and Coman and Trohman [8] (179 patient) also found an incidence of approximately 8%. The report of Klein et al [9] also indicated a relatively high incidence of 8 (16%) of 50 patients in a study where V1 lead was carefully checked for its correct position on the chest.…”
Section: Incidence From the Literaturementioning
confidence: 89%
See 2 more Smart Citations
“…Okmen et al [7] (300 patients) and Coman and Trohman [8] (179 patient) also found an incidence of approximately 8%. The report of Klein et al [9] also indicated a relatively high incidence of 8 (16%) of 50 patients in a study where V1 lead was carefully checked for its correct position on the chest.…”
Section: Incidence From the Literaturementioning
confidence: 89%
“…Almehairi et al [2] indicated that in 48 patients that an RV site is present with a transition ≤V3 yielding 96% sensitivity and 100% specificity. Okmen et al [7] had also evaluated precordial transition in 25 patients and found that a V3 transition resulted in a 97% sensitivity. Thus, precordial transition provides a high predictive value to rule out inadvertent LV pacing.…”
Section: Precordial Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the QRS with morphology RBBB during right ventricular pacing can be distinguished from the shape of the QRS with morphology RBBB during left ventricular pacing according to the criteria described by Okmen et al: left axis deviation to the left in the frontal plane between -30 and -90 degrees, the transition zone in V3 lead (R-wave amplitude equal to the S-wave amplitude), the lack of S-wave in lead I and the sets of qR or RS in V1 lead. Nevertheless, each case of RBBB in ECG requires an accurate assessment of the electrode location [6].…”
Section: Discussionmentioning
confidence: 99%
“…Coman and Trohman [5] and Okmen et al [6] suggested an algorithm to separate RV and LV pacing morphology by using frontal axis and precordial transition point. After exclusion of pacing from proximal and mid septum, if there is a frontal axis of 0 to 90 degrees and precordial transition is by V3 then uncomplicated RV pacing can be distinguished from LV pacing with a sensitivity, specificity and positive predictive value of 86%,99% and 95% respectively.…”
Section: Discussionmentioning
confidence: 99%